Pengaruh Kadar Air dan Kadar Asam Lemak Bebas Terhadap Masa Simpan Minyak Kelapa Mandar: The Influence of Water Content and Free Fatty Acid Content on Mandar Coconut Oil Shelf Life - Musafira; Dzulkifli; Fardinah; Nizar (KOVALEN: Jurnal Riset Kimia, 2020)
Mandar coconut oil made in Tulu village, Majene Regency, West of Sulawesi, is very popular among Sulawesi Barat people. It is because of the unique aroma which is not owned by other Mandar oil traders. In addition, according to Mandar coconut oil trader who is also the produsen of Mandar oil said that his coconut oil could be stored for months. This research aimed to know the influence of water content and free fatty acid content on Mandar coconut oil shelf life. Gravimetric Method and Alkaline method were used to determine the water content and the free fatty acid content respectively. The oil was stored at room temperature. Water content and free acid content were measured every week, i.e week zero to week four (5 observations). Shelf life estimation was done by applying the kinetic theory. The result shows that the water content and the free fatty acid content increase as shelf life increases. Mandar coconut oil can be stored at room temperature for 1 month, 12 days. Keywords: Mandar coconut oil, water content, free fatty acid, shelf life